The Role of Atypical Pathogens in Community-Acquired Pneumonia - Marrie, Thomas J.; Costain, Nicholas; La Scola, Bernard; Patrick, Ward; Forgie, Sarah; Xu, Zhaolin; McNeil, Shelly A. (Seminars in Respiratory and Critical Care Medicine, 2012)
The term atypical pneumonia was first used in 1938, and by the 1970s it was widely used to refer to pneumonia due to Mycoplasma pneumoniae, Legionella pneumophila (or other Legionella species), and Chlamydophila pneumoniae. However, in the purest sense all pneumonias other than the classic bacterial pneumonias are atypical. Currently many favor abolition of the term atypical pneumonia.This review categorizes atypical pneumonia pathogens as conventional ones; viral agents and emerging atypical pneumonia pathogens. We emphasize viral pneumonia because with the increasing availability of multiplex polymerase chain reaction we can identify the agent(s) responsible for viral pneumonia. By using a sensitive assay for procalcitonin one can distinguish between viral and bacterial pneumonia. This allows pneumonia to be categorized as bacterial or viral at the time of admission to hospital or at discharge from the emergency department and soon thereafter further classified as to the etiology, which should be stated as definite or probable.
Keywords: pneumonia; atypical; viral; community-acquired